Development, validation and use of an instrument for assessing business management learning environments in higher education in Australia: the Business Management Education Learning Environment Inventory (BMELEI) - Chien, Chee Fah (Curtin University, 2007)
Although there are numerous instruments available for assessing classroom learning environments at the tertiary level, no instrument has been specifically designed and validated for measuring the business management education learning environment (Brennan & Ahmad, 2005). My aims were (1) to design, develop and validate an instrument, the Business Management Education Learning Environment Inventory (BMELEI), for assessing business management students’ perceptions of the psychosocial learning environments of university seminars and tutorials and (2) to relate learning environment to attitudes towards the subject and attitudes towards the case study teaching strategy. This study is distinctive in that it involved both quantitative and qualitative methods. The BMELEI and two attitude scales were administered to 480 final-year undergraduate and postgraduate business studies students in 30 classes at both Curtin University of Technology and Edith Cowan University in Perth, Australia. The qualitative component of the study involved semi-structured interviews with 42 randomly-selected participants from the above universities. Factor analysis supported a six-factor structure (Student Cohesiveness, Teacher Support, Involvement, Task Orientation, Cooperation and Equity) with scale alpha reliabilities ranging from 0.78 to 0.90 for the actual form and from 0.80 to 0.92 for the preferred form using the individual as unit of analysis. Students’ attitudes were found to be positively associated with classroom learning environment.Also differences were found between students’ perceptions of the actual and preferred classroom environment, and between male and female students’ perceptions of the actual and preferred classroom environment. Findings suggested that students preferred a more positive and favourable classroom learning environment than they perceived as being actually present.